Ethnic discrimination on paper: uncovering realtors' willingness to discriminate with mystery mails. Issue 9 (21st May 2023) - Ghekiere, Abel; Lippens, Louis; Baert, Stijn; Verhaeghe, Pieter-Paul
ABSTRACT: Introducing a new method, we measure real estate agents' intentions to act upon a discriminatory request on the housing market. Our results show that realtors are willing to discriminate on request and that the method of mystery mails allows scholars to measure and contextualize these discriminatory intentions in a detailed and elaborate way.